KONTRIBUSI PEMUNGUTAN PAJAK OLEH BENDAHARA PENGELUARAN PEMERINTAH TERHADAP PENERIMAAN PAJAK PENGHASILAN PADA KPP PRATAMA MANADO TAHUN 2013-2017 - Padang, Elyakim Tande; Sondakh, Jullie J.; Mawikere, Lidia M. (Universitas Sam Ratulangi, 2018)
Government Expenditure Treasurer is a party that carries out tax deduction from expenditures originating from State Revenue and Expenditure Budget or Regional Revenue and Expenditure Budget. This study aims to know the contribution of tax collection by the government treasurer of income tax revenues at the KPP Pratama Manado Year 2013-2017. The method of analysis in this research is quantitative associative by using contribution analysis technique. In accordance with the classification table of contribution criteria it can be seen that the rate of tax collection contribution by the Government Treasury is high or strongly contribute to income tax revenue in KPP Pratama Manado Year 2013-2017.Keywords: Contribution of Tax Collection, Tax Receipts